노년기 정신장애의 전기경련치료 - 주은정; 김희철; 강웅구; 이남영; 박승현; 김정민; 김용식; 정인원; Joo, Eun-Jeong; Kim, Hee Cheol; Kang, Ung Gu; Lee, Nam Young; et al. (Journal of the Korean Society of Biological Psychiatry, 2020)
Electroconvulsive therapy (ECT) is indicated for various mental disorders (e.g., major depressive disorder, schizophrenia, and bipolar disorder) and the behavioral and psychological symptoms of dementia in elderly patients. Furthermore, ECT is a useful first-line treatment in emergency and crisis situations such as suicide risk, violent behavior, catatonia, and food refusal, which are more frequent in elderly patients. ECT is also effective in the treatment of the motor symptoms of neurological disorders, such as Parkinson's disease and Huntington's disease. Due to the high risk of various physical diseases, the comorbid physical conditions of elderly patients should be individually controlled to optimize ECT treatment. Compared to young adults, in elderly patients the seizure threshold is higher, the seizure duration is shorter, and the anesthetic dose is lower. On the contrary, the response rate in the elderly is both faster and higher. Considering potential cognitive decline and the prevention of further deterioration of cognitive function in elderly patients, in the absence of significant comorbidities, twice weekly sessions and right unilateral electrode placement with a lower seizure threshold and less cognitive effect are preferred to bilateral electrode placement, which has a high risk of adverse cognitive effects. After an acute course of ECT, continuation and maintenance of ECT, combined with prescription of therapeutic drugs, may prevent possible relapse or recurrence of mental disorders. In conclusion, ECT can be used to treat mental disorders in elderly adults, with safety and effectiveness comparable to that in young adults.